Glial remodeling during metamorphosis influences the stabilization of motor neuron branches in Drosophila. - Hebbar, S.; Fernandes, J.J. (Developmental Biology, 2010)
Motor neurons that innervate the dorsal longitudinal (flight) muscles, DLMs, make multiple points of contact along the length of fibers. The stereotypy of the innervation lies in the number of contact points (CPs) made by each motor neuron and is established as a consequence of pruning that occurs during metamorphosis. Coincident with the onset of pruning is the arrival of glial processes that eventually ensheath persistent branches. To test a possible role for glia during pruning, the development of adult-specific glial ensheathment was disrupted using a targeted expression of dominant negative shibire. Such a manipulation resulted in fewer contact points at the DLM fibers. The development of innervation was examined during metamorphosis, specifically to test if the reduction was a consequence of increased pruning. We quantified the number of branches displaying discontinuities in their membrane, an indicator of the level of pruning. Disrupting the formation of glial ensheathment resulted in a two-fold increase in the discontinuities, indicating that pruning is enhanced. Thus glial-neuronal interactions, specifically during pruning are important for the patterning of adult innervation. Our studies also suggest that FasII plays a role in mediating this communication. At the end of the pruning phase, FasII localizes to glia, which envelops each of the stabilized contact points. When glial FasII levels are increased using the Gal4/UAS system of targeted expression, pruning of secondary branches is enhanced. Our results indicate that glia regulate pruning of secondary branches by influencing the balance between stabilization and pruning. This was confirmed by an observed rescue of the innervation phenotype of FasII hypomorphs by over expressing FasII in glia.